The Effect of Foliar and Soil Application of Flufenacet and Prosulfocarb on Italian Ryegrass (Lolium multiflorum L.) Control - Christian Andreasen; Kasper Lund Høgh; Signe Marie Jensen (Agriculture, 2020)
Italian ryegrass (Lolium multiflorum Lam.) can be a troublesome weed that may causes high yield losses to several crops. Ryegrass resistance to the typically used acetolactate synthase (ALS) and acetyl-CoA carboxylase (ACCase) inhibiting herbicides complicates the control. As an alternative, we evaluated and compared the effects of two soil-acting herbicides, flufenacet and prosulfocarb, on susceptible L. multiflorum. The herbicides were applied in two doses in three different methods of applications: (1) soil and foliar application (2) foliar application, and (3) soil application only. Two greenhouse experiments separated in time showed that both herbicides reduced root and foliar biomass significantly as compared to the nontreated plants. In experiment 1, both herbicides resulted in lower efficacy when they only were applied to the leaves compared to the nontreated plants. Especially the foliar effect of flufenacet was small. The highest dose of prosulfocarb (4200 g ai ha−1) reduced the fresh foliar weight by 61% in experiment 1 and by 95% in experiment 2. The lowest dose of prosulfocarb (2100 g ai ha−1) reduced the weights by 73% (experiment 1) and 98% (experiment 2), respectively. For both herbicides the soil and foliar application applied postemergence were effective in reducing growth of L. multiflorum significantly in both experiments. Foliar application showed inconsistent results, showing that soil absorption plays an important role on herbicide efficacy even when the herbicides are applied postemergence. Postemergence application of prosulfocarb and flufenacet were effective to reduce L. multiflorum growth having apparently good root and leaf absorption.